Computational exploration of microRNAs from expressed sequence tags of Humulus lupulus, target predictions and expression analysis. (December 2015) - Mishra, Ajay Kumar; Duraisamy, Ganesh Selvaraj; Týcová, Anna; Matoušek, Jaroslav
Graphical abstract: Highlights: Twenty-two miRNAs belonging to 17 miRNA families were identified in hop following comparative computational approach and EST-based homology search according to a series of filtering criteria. The total of 47 potential miRNA targets were identified for predicted 22 miRNAs. The new miRNAs identified in this study should enable investigation of the complexity of miRNA-mediated genes network in understanding their roles in regulating growth, development, metabolism, and other physiological processes. Abstract: Among computationally predicted and experimentally validated plant miRNAs, several are conserved across species boundaries in the plant kingdom. In this study, a combined experimental- in silico computational based approach was adopted for the identification and characterization of miRNAs in Humulus lupulus (hop), which is widely cultivated for use by the brewing industry and apart from, used as a medicinal herb. A total of 22 miRNAs belonging to 17 miRNA families were identified in hop following comparative computational approach and EST-based homology search according to a series of filtering criteria. Selected miRNAs were validated by end-point PCR and quantitative reverse transcription-polymerase chain reaction (qRT-PCR), confirmed the existence of conserved miRNAs in hop. Based on the characteristic that miRNAs exhibit perfect or nearly perfect complementarity with their targeted mRNA sequences, a total of 47 potential miRNA targets were identified in hop. Strikingly, the majority of predicted targets were belong to transcriptional factors which could regulate hop growth and development, including leaf, root and even cone development. Moreover, the identified miRNAs may also be involved in other cellular and metabolic processes, such as stress response, signal transduction, and other physiological processes. The cis -regulatory elements relevant to biotic and abiotic stress, plant hormone response, flavonoid biosynthesis were identified in the promoter regions of those miRNA genes. Overall, findings from this study will accelerate the way for further researches of miRNAs, their functions in hop and shows a path for the prediction and analysis of miRNAs to those species whose genomes are not available.